A measurement of quality costs in industrial organizations - Riyadh Y. Alsada; Yathish Kumar (Cogent Business & Management, 2022)
This paper aims to determine the level of awareness and implementation of measuring CoQ in MIEs in Yemen. In contrast, this study was based on the traditional CoQ Prevention-Appraisal-Failure (PAF) model. Also, this paper proposes a suitable model for measuring CoQ in MIEs based on the research results. The Applied research focused on large companies where CoQ programs in the majority of companies operate as a subsystem of underlying management. Managers of large companies use indicators to control and evaluate performance for production quality. Still, they usually do not develop a separate framework for measuring and assessing CoQ. As a result, this research attempted to answer the question, Are Yemeni industrial companies interested in measuring, analyzing, and reporting CoQ items (prevention, appraisal, and failure costs) concerned in their industry? It also determines the extent these companies are interested in measuring, and analyzing hidden CoQ. According to this research findings, most major companies in Yemen are aware of and practice measuring CoQ. At the same time, the study showed that these companies are still not interested in measuring the hidden CoQ in their manufacturing.
Keywords: 650; costs of quality (CoQ); hidden CoQ; major industrial enterprises (MIEs); measurement of CoQ; model for controlling CoQ